1979
DOI: 10.1139/v79-260
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis of the Lythraceae alkaloids. I. The lysine-derived fragment

Abstract: The biosynthesis of decodine (7) and decinine (9), Lythraceae alkaloids containing a trans-fused quinolizidine nucleus, was studied in intact plants of Decodonverticillatus (L.) Ell. Nonrandom incorporation of radioactivity from 14C-labelled samples of lysine, cadaverine, and Δ1-piperideine was demonstrated by partial degradation. Pelletierine did not serve as a precursor of the alkaloids. It was also shown, by means of 3H,14C-labelled tracers, that the alkaloids are derived from L-lysine whereas pipecolic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
(20 reference statements)
3
17
0
Order By: Relevance
“…The experiment with [3-14C]phenylalanine (experiment 11) showed that the distribution of label within decodine (5) in D. verticillatus (C-13 58%, C-1 33%) was very similar to that found earlier in cryogenine (25) derived from the same precursor in H. salicifolia (C-13 61%, C-1 31%(3), C-13 46%, C-1 33% (26)), indicating a close correspondence in the origin of two alkaloids of different ring stereochemistry in two different plant species.…”
Section: (1)supporting
confidence: 68%
See 4 more Smart Citations
“…The experiment with [3-14C]phenylalanine (experiment 11) showed that the distribution of label within decodine (5) in D. verticillatus (C-13 58%, C-1 33%) was very similar to that found earlier in cryogenine (25) derived from the same precursor in H. salicifolia (C-13 61%, C-1 31%(3), C-13 46%, C-1 33% (26)), indicating a close correspondence in the origin of two alkaloids of different ring stereochemistry in two different plant species.…”
Section: (1)supporting
confidence: 68%
“…Alkaloids with trnt~s-ringjunction cis-ring junction e.g., decodine (5) and e.g., vertine (25) and decinine (6) decamine ( found in cryogenine (25) in H. salicifolia (3,26). The distribution of label in the alkaloids obtained in experiment 12 is entirely different.…”
Section: Alkaloids Withmentioning
confidence: 95%
See 3 more Smart Citations